1995
DOI: 10.1007/bf02331907
|View full text |Cite
|
Sign up to set email alerts
|

Neural regulation of sex-pheromone glands in Lepidoptera

Abstract: Substantial progress has been made toward understanding the neuroendocrine regulation of sexpheromone glands in Lepidoptera, but several recent studies have revealed that direct contact of the pheromone gland with blood-borne factors is not necessary to induce pheromone biosynthesis and release in some species. The nervous system provides an alternate route of activanon. Evidence from several species indicates that the pheromone gland IS innervated and regulated by neural activity. Electrical stimulation of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…It has been proposed, however, that the innervation of the pheromone gland is crucial for pheromonotropic activity and that the biogenic amine, octopamine, may be involved as an intermediate messenger during the stimulation of sex pheromone production in Lepidoptera (Christensen et al, 1991(Christensen et al, , 1992Christensen and Hildebrand, 1995). Ventral nerve cord (VNC) stimulation and injections of octopamine to mid-photophase females resulted in the stimulation of pheromone biosynthesis (Christensen et al, 1991).…”
Section: Target Tissuesmentioning
confidence: 99%
“…It has been proposed, however, that the innervation of the pheromone gland is crucial for pheromonotropic activity and that the biogenic amine, octopamine, may be involved as an intermediate messenger during the stimulation of sex pheromone production in Lepidoptera (Christensen et al, 1991(Christensen et al, , 1992Christensen and Hildebrand, 1995). Ventral nerve cord (VNC) stimulation and injections of octopamine to mid-photophase females resulted in the stimulation of pheromone biosynthesis (Christensen et al, 1991).…”
Section: Target Tissuesmentioning
confidence: 99%
“…Hormonal regulation of the sex-pheromone gland of M. sextu does not preclude the possibility that the gland is also regulated, in part, by a descending neural pathway. The evidence for neural regulation of the sexpheromone gland of moths has been reviewed by Christensen and Hildebrand (1995), and these authors report that bath application of PBAN to the terminal abdominal ganglion of M. sextu results in activation of certain efferent cells of this ganglion. Moreover, Thyagaraja and Raina (1994) have shown that in L. dispar, severance of the ventral nerve cord blocks pheromone production and application of PBAN to the severed terminal abdominal ganglion results in significant pheromone production.…”
Section: Pban and The Regulation Of The Sex-pheromone Glandmentioning
confidence: 99%
“…There remain uncertainties regarding the role of PBAN in the control of the pheromone gland of female Lepidoptera (Christensen and Hildebrand, 1995). In addition, PBAN is known to occur in larvae and in adult male Lepidoptera, but its function in these insects is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption has been corroborated by subsequent work (Hollander and Yin, 1985;Tang et al, 1987;Thyagaraja and Raina, 1994) and a neuronal input descending from the brain/subesophageal ganglion and intact connections all the way to the TAG seem required in the regulation of the gypsy moth pheromone production (Thyagaraja and Raina, 1994). Evidence from several moth species indicates that the pheromone gland is innervated and regulated by TAG neurons and that neural stimulation from the TAG significantly increases the pheromone production and dispersal (see Christensen et al, 1991;Christensen and Hildebrand, 1995). Interestingly, the biogenic monoamine octopamine appears involved in this process in some moths (Christensen et al, 1991(Christensen et al, , 1992Christensen and Hildebrand, 1995).…”
Section: Discussionmentioning
confidence: 73%
“…Evidence from several moth species indicates that the pheromone gland is innervated and regulated by TAG neurons and that neural stimulation from the TAG significantly increases the pheromone production and dispersal (see Christensen et al, 1991;Christensen and Hildebrand, 1995). Interestingly, the biogenic monoamine octopamine appears involved in this process in some moths (Christensen et al, 1991(Christensen et al, , 1992Christensen and Hildebrand, 1995). We have detected octopamine-like immunoreactive neurons in the L. dispar TAG, as well as colocalization of octopamine-like immunoractive material and the retrogradely transported tracer tetramethylrhodamineconiugated dextran amine (TMR-DA) in a number of TAG neurons TMR-DA backfilled via the 4th-6th TAG nerves (Boi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%